Composite materials a vision for the future - Nicolais, Luigi; Meo, Michele; Milella, Eva.; SpringerLink (Online service). (London Springer, 2011)
Composite Materials presents recent developments and state-of-the-art achievements in the science and technology of composites. It identifies and discusses key and emerging issues for future progress in the multidisciplinary field of composites. By bringing together leading experts and promising innovators from research institutions and academia, Composite Materials highlights unresolved issues and identifies opportunities for long-term research needs to provide the reader with a vision for the future in various fields of application of composite materials. A few of the many future directions highlighted in the book are increasingly multifunctional properties; complex, hybrid and nanoreinforced materials; and tailoring in multiple dimensions and directions. The wider areas covered include, but are not limited to, the following: biomedical engineering, civil engineering, aerospace engineering, automotive engineering, and naval engineering. Composite Materials is designed to increase the reader?s understanding of the state of the art of composite materials in a variety of industrial sectors and to explore future needs and opportunities. It will therefore be of use to professionals working in the composites industry, research centers, and academia, who already have a graduate-level knowledge of composite materials.
1. Future composite structures: from metal mimics to composite constructions -- 2. Opportunities for polymeric-based composite applications: enhanced toughness materials and molded discontinuous short fiber composite technology for transport aircraft parts and component application -- 3. Composite materials for marine applications - key challenges for the future -- 4. multifunctional polymer-based structures for human tissues reconstruction -- 5. Textile-reinforced and polymer-modified mortars (TRM): a new generation of composite materials for strengthening and seismic retrofitting of structures -- 6. Current and future applications of polymer composites in the field of tribology -- 7. Graphite nanoplatelet composites and their applications -- 8. Developments in characterising the structural behaviour of composites in fire.
Electronic reproduction.
Keywords: Composite materials; Electronic books